Laparoscopically assisted treatment of imperforate hymen in a patient with ventriculo-peritoneal (VP) shunt for congenital hydrocephalous: A case report. (2018) - Sorrentino, Felice; Angioni, Stefano; Pontis, Alessandro; Greco, Francesca; Scutiero, Gennaro; Nappi, Luigi
Abstract: Introduction: We report a case of laparoscopically assisted treatment of imperforate hymen in a patient with ventriculo-peritoneal (VP) shunt for congenital hydrocephalous. Presentation of case: The patient presented primary amenorrhea and cyclical abdominal pain. At clinical examination a painful mass in the abdomen and normal secondary sex characteristics were observed. Perineal examination showed a bulging hymen and transabdominal ultrasonography and CT scan revealed a dense mass in the pelvis and abdomen. We diagnosed an imperforate hymen with haematocolpos and haematometra. The surgical procedure was performed under laparoscopic guidance in order to check the pelvic anatomy inside, to exclude the presence of adhesions and endometriotic lesions and to evaluate the ventriculo-peritoneal (VP) shunt. Discussion: Imperforate hymen (IH) is the most common obstructive congenital anomaly of female genital tract. It is potentially accompanied by other female reproductive tract anomalies, suggesting a multifactorial genetic etiology. It usually presents during puberty, causing accumulation of menstrual products in the vagina (haematocolpos) or in the uterus (haematometra). Generally, the treatment consists in hymenotomy or hymenectomy, that allows the accumulated blood to be drained away. Laparoscopically assisted treatment of imperforate hymen is not routinely performed but it can be considered in particular clinical conditions. It is a viable procedure very useful to exclude female reproductive anomalies, the presence of pelvic pathology (adhesions and endometriosis) and to evaluate the ventriculo-peritoneal (VP) shunt and its possible complications (abdominal pseudocyst). Conclusion: This is the first case of laparoscopically assisted treatment of imperforate hymen in a patient with ventriculo-peritoneal (VP) shunt for congenital hydrocephalous. Laparoscopic guidance has to be considered to exclude other female reproductive anomalies, pelvic pathology and abdominal complications (shunt dysfunction and abdominal pseudocyst). Highlights: Imperforate hymen (IH) is the most common obstructive congenital anomaly of female genital tract. It is potentially accompanied by other female reproductive tract anomalies. The treatment is always represented by hymenotomy or hymenectomy. Laparoscopically assisted treatment of IH is useful to exclude other female reproductive anomalies and pelvic pathology. It is indicated in patients with VP shunt to exclude abdominal complications (blockage of the system, abdominal pseudocyst).